Optimizing Tax Revenue Through Strategic Management Utilizing Tax Gap Dashboard In Indonesia - Barus, Dionisius Christian Hamdany; Silalahi, Heriantonius; Kurnia, Budi (Educoretax, 2024)
Tax revenue plays a crucial role in the development and sustainability of a nation. However, significant challenges are faced in optimizing tax revenue, including tax compliance issues and the imbalance between the tax obligations that should be paid by taxpayers and what is actually paid. To address these challenges, it is important to implement effective strategies and appropriate technology in tax administration. This research aims to analyze the optimization of tax revenue through a strategic management approach utilizing the Tax Gap dashboard by the Directorate General of Taxes. Using a qualitative method, this study seeks to gain an in-depth understanding of the concept of strategic management and the implementation of the Tax Gap dashboard in the context of tax administration. The qualitative method was chosen because it allows for a deeper exploration of the strategies employed by the Directorate General of Taxes as well as a more holistic understanding of the role of the Tax Gap dashboard technology in enhancing tax administration effectiveness. Data collection methods in this study were conducted through a thorough review of literature related to the research topic, such as academic journals, articles, government reports, and other official sources. In this process, the researcher investigated various data sources to gather relevant information about the implementation of tax management strategies and the utilization of the Tax Gap dashboard by the Directorate General of Taxes. The conclusion of this research summarizes the main findings and provides recommendations for improving the effectiveness of strategies implemented by the Directorate General of Taxes.